Optimized Hybrid Modulation Algorithm to Control Large Unbalances in Voltage and Intensity in the NP Point of an NPC Converter - Gálvez, Manuel; Rodríguez, F. Javier; Bueno, Emilio (IntechOpen, 2012)
None